Fatty acid compostion of selected vietnamese biscuites including trans-isomers - Quoc Tuan, Hoang; Hong Son, Vu; Thi Minh Tu, Nguyen (Vietnam Journal of Science and Technology, 2017)
In this study, fatty acid compositions including trans-isomers contents of selected Biscuits products produced by Vietnamese confectionery companies and imported products purchased from Hanoi markets were determined by gas chromatography. Palmitic acid and oleic acid were the most abundant, with concentrations ranged from 21 % to 52 %, and 23 % to 43 %, respectively, and followed by linoleic acid, lauric acid, myristic acid. The saturated, cis-monounsaturated and cis-polyunsaturated fatty acid contents were within ranges of 37 % - 75 %, 18 % - 43 %, 0.4 – 26 % of total fatty acid methyl ester, respectively. Trans-fatty acids were identified in all samples excepted brands B3, B13, B17, B24*, and the contents ranged from 0.07 % to 7,16 %. A considerable variability in fatty acid composition of biscuits which indicated that different types of fats and oils were used for production of selected Vietnamese biscuits and imported products was showed by these results got from the study.